Hemolytic anemia due to experimental onion poisoning in Iranian Ghezel sheep - Y Haji-Sadeghi; M Fartashvand; M Shokouhi; S.R Bahavarnia (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2012)
This study was conducted on 10 male Iranian Ghezel sheep. To ensure the health of livestock and deworming treatment, sheep were kept without any intervention and on a normal and high quality diet for a month. Then onion was added to the animal's diet gradually, and after a week sheep were fed only with onions. Animals were fed with onions for 10 weeks, regular and weekly blood sampling was done during this period. Clinical findings included anemia, paleness of mucus membranes, tachycardia, weakness, lethargy and death in some cases. Red blood cell counts, hemoglobin and hematocrit decreased from week 1, reaching to a significant low on week 3 (p